2013
DOI: 10.1111/flan.12030
|View full text |Cite
|
Sign up to set email alerts
|

Oral Proficiency Standards and Foreign Language Teacher Candidates: Current Findings and Future Research Directions

Abstract: The renewed national focus on teacher quality and effectiveness has resulted in more rigorous standards that describe the knowledge and skills required of teacher candidates across all disciplines. In the area of foreign languages, three sets of professional standards address the oral proficiency of teachers in the target languages they teach across the career continuum. For teacher candidates, the ACTFL/NCATE Program Standards for the Preparation of Foreign Language Teachers (2002) establish minimum oral prof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
61
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(67 citation statements)
references
References 22 publications
4
61
1
Order By: Relevance
“…The presence of native speakers of the foreign language was mentioned in a large‐scale study by Swender, Surface, and Hamlyn () that reported slightly higher results. In that study, 59.5% of the teacher candidates achieved the ACTFL requirement of Advanced Low (information available in Glisan et al, , p. 70). More recent research has continued to demonstrate that approximately half of foreign language teacher candidates are able to successfully reach oral proficiency expectations determined by the ACTFL.…”
Section: Literature Reviewmentioning
confidence: 89%
“…The presence of native speakers of the foreign language was mentioned in a large‐scale study by Swender, Surface, and Hamlyn () that reported slightly higher results. In that study, 59.5% of the teacher candidates achieved the ACTFL requirement of Advanced Low (information available in Glisan et al, , p. 70). More recent research has continued to demonstrate that approximately half of foreign language teacher candidates are able to successfully reach oral proficiency expectations determined by the ACTFL.…”
Section: Literature Reviewmentioning
confidence: 89%
“…In general, Spanish candidates are required to obtain higher scores than their French and German colleagues. This is particularly interesting given the findings of Glisan, Swender, and Surface () noting that fewer Spanish candidates attained the Advanced‐Low level on the OPI when compared to French candidates.…”
Section: Verifying Candidates' Knowledge Skills and Dispositionsmentioning
confidence: 85%
“…1 Google+ and the student module of Schoolshape can be operated on handheld mobile devices, but what is of greater importance is the fact that students can access course resources on whatever tablet, laptop, or desktop computer happens to be at hand, anywhere there is a broadband Internet connection. Together, Google+ and Schoolshape provide the means to extend learning out of the classroom into the real world, to free it from time constraints, to store, access and share information for collaborative tasks and, most importantly, to scaffold pedagogical exercises.…”
Section: Exploiting Ubiquitous Instructional Technologymentioning
confidence: 99%
“…Even in well-endowed educational systems such as those in American universities, the range of foreign language competency among graduating language majors can be judged by the fact that nearly half (46%) score below Advanced-low according to the American Council on the Teaching of Foreign Languages scale in teacher certification exams [1]. Moreover, median scores on competency level tests over the past 50 years in the US mask a pervasive inconsistency in foreign language competency that ranges "from abysmally poor to superior performance" [2] (p. 134).…”
Section: Introductionmentioning
confidence: 99%